The answer is B, all you have to do is combine like terms 8x+9x and 12+ -3
Answer: 3/2
Step-by-step explanation:
We can start by converting 3 1/3 to an improper fraction. Since 3 is equal to 9/3, 3 1/3 would be equal to 9/3 + 1/3 = 10/3.
Therefore, we are doing
.
Dividing 5 by 10/3 is the same as multiplying 5 and the reciprocal of 10/3, which is 3/10.
5*3/10 = 15/10 = 3/2.
You can use the Pythagorean theorem, a^2+b^2=c^2, to solve this.
b= square-root of (c^2)-(a^2)
b= square-root of (9^2)-(2^2)
b= 8.77.... which in the exact form is square root of 77.
13x because you are saying the product of 13 that means 13x